A batucada de samba em Córdoba, Argentina - Bertazzoli, Caio Fiori (2023)
This work presents and discusses the results from a research with the samba batucada ensembles that are present in Córdoba, Argentina, arising from the case study of three groups from the region: Batería Cadencia Cordobesa, Acadêmicos de Manos de Fuego and Escola de Samba União da Serra. With a focus on percussion and considering contextual aspects, the research seeks to understand the musical practices of the groups’ samba batucada, a popular manifestation that is not traditionally from the region. The research is methodologically supported by field research, aided by the researcher’s previous nine years experience in the country. The field research included the recording of audiovisual material, pre existing recordings from the groups and interviews that were held on field with each groups’ respective leader and other persons that participate in the context. The analysis and interpretations are based on the ethnomusicological field and related areas of study, fundamentally the studies related to samba batucada musical practices. The results show that the groups work within a shared cultural context but with specificities and and reinterpretations of the samba’s musical elements that are unique to each one. Such interpretations are part of a process that involves a transcultural interaction between the subjects of the cultural and social cordobes context and the batucada samba universe.